Seelsorge als Denkdiakonie. Reformatorisches Erbe in der heutigen Seelsorge - Dávid NÉMETH (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica, 2017)
Pastoral Counseling as Deaconry. Reformed Direction in Contemporary Pastoral Care.